2017
DOI: 10.1177/1556264617696921
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Decision-Making Involvement About Research Participation: Associations With Perceived Fairness and Self-Efficacy

Abstract: The primary objective of this study was to examine the associations of children’s involvement in decisions about research participation with their perceptions of the decision making process and self-efficacy. Participants were children (ages 8–17) who enrolled in research studies in the prior two months. Children completed a questionnaire that yielded three decision making involvement subscales: Researcher Engages Child; Researcher Supports Autonomy; and Child Participates. Children reported on fairness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 51 publications
2
25
0
4
Order By: Relevance
“…The perceptions survey included three questions that have been previously described. 36 Questions included “How easy was it to understand the information that was discussed during your clinic visit today?”, “How much of a voice did you have in the clinic visit today?”, and “How satisfied are you with communication between you and your doctor today?”. Each item had a four-point Likert-type response scale: not much/not very, a little bit, quite, and very/a lot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceptions survey included three questions that have been previously described. 36 Questions included “How easy was it to understand the information that was discussed during your clinic visit today?”, “How much of a voice did you have in the clinic visit today?”, and “How satisfied are you with communication between you and your doctor today?”. Each item had a four-point Likert-type response scale: not much/not very, a little bit, quite, and very/a lot.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the study reports single-item measures, which are more susceptible to random error and lower construct validity, because they are less likely to account for all facets of a construct. 47 However, the single-item measures used have been previously reported to describe children’s perceptions in medical settings, 36 and child satisfaction related to observed participation has rarely been previously measured in any form.…”
Section: Limitationsmentioning
confidence: 99%
“…More focus on the researcher-child interaction in the decision-making process has been found to be likely to improve children's perception of research and to make it more meaningful [19]. Yet little empirical data is available on how the relationship between children and doctors influences children in research [20].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, prior cross-sectional research using a new measure of DMI, called the Decision Making Involvement Scale (DMIS), found that more youth expression of opinions and information during decision-making interactions with parents was associated with better adherence in youth with T1D after controlling for age (Miller & Jawad, 2014). Prior research using the DMIS also found that when children perceived that adults engaged them more in decision-making about research participation, they reported higher decision self-efficacy (Miller, Feudtner, & Jawad, 2017).…”
mentioning
confidence: 99%